Donec formetur Christus in vobis (Ga 4,19). From Eikonic Soteriology to Mimetis Parenesis - Sztuk , Dariusz (Towarzystwo Naukowe Franciszka Salezego (TNFS), 2022)
In reflection dedicated to the relations between theological arguments and parenesis in St. Paul’s epistolarium, there is a general agreement as to the fact that ethical exhortations are usually motivated by the doctrinal passages of the letters of the Apostle Paul, or, that they are woven into the argumentative substance of a given letter. Without denying this fact, it seems that the relationship between the two parts of the letters can be described in a different way. Namely, due to the fact that their doctrinal part presents the image of Christ and His work of salvation, we can characterize soteriology as iconic. This is possible because its agens is itself an icon. In other words, Paul’s Christology is iconic because Christ is the ‘image of God’ and, consequently, His work present in the cross, the sign of salvation, is also iconic. Soteriology remains related to the ethical part of the letters and, because St. Paul in different ways encourages his recipients to follow and to be like Christ, it will be justified to define his parenesis as mimetic. W rozważaniach poświęconych związkom między argumentami teologicznymi a parenezą w epistolarium św. Pawła panuje powszechna zgoda co do tego, że napomnienia etyczne są zwykle motywowane doktrynalnymi fragmentami listów Apostoła Pawła lub że są utkane z w treść argumentacyjną danego listu. Nie zaprzeczając temu faktowi, wydaje się, że relacje między obiema częściami listów można opisać w inny sposób. Mianowicie ze względu na to, że ich część doktrynalna przedstawia obraz Chrystusa i Jego dzieła zbawienia, możemy scharakteryzować soteriologię jako ikoniczną. Jest to możliwe, ponieważ jego agenci sami są ikonami. Innymi słowy, chrystologia Pawła jest ikoniczna, ponieważ Chrystus jest „obrazem Boga”, a zatem Jego dzieło obecne w krzyżu, znaku zbawienia, jest również ikoniczne. Soteriologia pozostaje w związku z etyczną częścią listów, a ponieważ św. Paweł w różny sposób zachęca swoich odbiorców do naśladowania i upodobniania się do Chrystusa, zasadne będzie ...